Cooperative elastic switching vs. laser heating in [Fe(phen)2(NCS)2] spin-crossover crystals excited by a laser pulse. Issue 38 (16th May 2016) - Bertoni, R.; Lorenc, M.; Graber, T.; Henning, R.; Moffat, K.; Létard, J.-F.; Collet, E.
Abstract : Ultrafast photoswitching in spin-crossover crystals induces lattice expansion, which drives cooperative and self-amplified spin-state transformation. Abstract : Spin-crossover crystals show multi-step responses to femtosecond light excitation. The local molecular photo-switching from low to high spin states occurs on the sub-picosecond timescale. It is followed by additional conversion due to elastic (ns) and thermal (μs) effects. In [Fe(phen)2 (NCS)2 ] crystals discussed herein, the thermal switching can be made unobtrusive for the investigation of cooperative elastic switching. We evidence a cooperative transformation induced by lattice expansion through elastic coupling between molecules in the crystal, where up to 3 molecules are transformed per photon.